A COMPREHENSIVE APPROACH TO THE QUALITY MILITARY HUMAN RESOURCES POLICY – THE PROFESSIONAL-PSYCHOPHYSIOLOGICAL SELECTION IN THE ARMED FORCES OF UKRAINE - Pampukha, I.; Makarchuk, M.; Filimonova, N.; Popkov, B.; Nikolaichuk, G.; Motyka, S.; Loza, V.; Kalnysh, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
According to the analysis of recent domestic and foreign publications on the professional suitability of military personnel, the current state of the human resources policy implementation in the Armed Forces of Ukraine requires improvement, focusing on enhancing the efficiency of fulfilling duties corresponding to the military occupational speciality. Therefore, there is no doubt about the importance of improving approaches to the professional psychophysiological selection of military personnel at the moment. It is due to the fact that the Law of Ukraine "On Labor Protection" states that "a person shall be admitted to perform high-risk works and works requiring a professional selection upon a conclusion of a psychophysiological expertise". The conclusion reflects "the person’s compliance (non-compliance) with the requirements of specific activities in strenuous and (or) dangerous conditions in terms of professionally important psychophysiological qualities". It should also be mentioned that modern military operations where the personnel perform complex missions with considerable risk in conditions of extreme uncertainty and danger require the military personnel a high intensity of making adequate and prompt decisions characterized by a considerable level of readiness to perform the assigned missions and accompanied by a significant physical and emotional load. Therefore this personnel should undergo a thorough evaluation of professionally important qualities to determine their professional suitability to perform the assigned missions, including in combat conditions. In any high-risk profession, the professional activity is performed due to individuals possessing slightly different psychophysiological and psychological profiles of professionally important qualities. Such service personnel can successfully perform the job of a specific professional activity. Justifying this conclusion is of great importance for the further improvement of professional selection techniques. The authors conducted a study to analyze and justify the hypothesis that there are equipotential profiles of professionally important qualities among individuals with the same level of professional suitability and developed suggestions for improving the professional selection techniques accordingly. The outcome of the study is the justification and development of a new paradigm for the professional selection of military personnel whose work is associated with increased danger. A new element in this paradigm is the statement that there are many equipotential professional profiles providing the basis for the successful professional activity of service personnel with different categories of professional suitability. The authors have formulated and justified the hypothesis that in every profession burdened with hazardous work, there are objectively individuals with the same professional suitability category who have equipotential profiles of professionally important qualities. New technology for developing the criteria of professional suitability of persons whose work is associated with increased danger has been suggested thereby. Using such profiles will allow improving the quality of the professional selection.